Antigen Cross-Presentation of Immune Complexes - Platzer, Barbara; Stout, Madeleine M.; Fiebiger, Edda (Frontiers in Immunology, 2014)
The ability of dendritic cells (DC) to cross-present tumor antigens has long been a focus of interest of physicians, as well as basic scientists, that aim to establish efficient cell-based cancer immune therapy. A prerequisite for exploiting this pathway for therapeutic purposes is a better understanding of the mechanisms that underlie the induction of tumor-specific cytotoxic T-lymphocyte (CTL) responses when initiated by DCs via cross-presentation. The ability of humans DC to perform cross-presentation is of utmost interest as this cell type is a main target for cell-based immunotherapy in humans. The outcome of a cross-presentation event is guided by the nature of the antigen, the form of antigen uptake and the subpopulation of DCs that performs presentation. Generally, CD8+ DCs are considered to be the most potent cross-presenting DCs. This paradigm, however, only applies to soluble antigens. During adaptive immune responses, immune complexes form when antibodies interact with their specific epitopes on soluble antigens. Immunoglobulin G (IgG) immune complexes target Fc-gamma receptors on DCs to shuttle exogenous antigens efficiently into the cross-presentation pathway. This receptor mediated cross-presentation pathway is a well-described route for the induction of strong CD8+ T cell responses. IgG-mediated cross-presentation is intriguing because it permits the CD8- DCs, which are commonly considered to be weak cross-presenters, to efficiently cross-present. Engaging multiple DC subtypes for cross-presentation might be a superior strategy to boost CTL responses in vivo. We here summarize our current understanding of how DCs use IgG-complexed antigens for the efficient induction of CTL responses. Because of its importance for human cell therapy, we also review the recent advances in the characterization of cross-presentation properties of human DC subsets.